Hubungan Masa Kerja dan Sikap dengan Perilaku Penggunaan Alat Pelindung Diri pada Petani Penyemprot Pestisida - Megawati Megawati; Putri Riskina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The use of Personal Protective Equipment (PPE) among pesticide-spraying farmers in developing countries remains low, increasing the risk of acute and chronic poisoning. Work tenure and attitude are suspected as the main determinants of this behavior, yet contextual empirical studies in rural Aceh remain limited. This study aimed to analyze the relationship between work tenure and attitude with PPE use behavior among rice farmers during pesticide spraying in Alue Gureb Village, East Peureulak District, East Aceh Regency. A quantitative analytic cross-sectional design was applied to 77 respondents selected via stratified random sampling from a population of 336 farmers. Data were collected using structured questionnaires and PPE observation checklists. Bivariate analysis used Chi-Square tests with α = 0.05. Results showed 59.7% of farmers did not use complete PPE. There was a significant relationship between work tenure and PPE use behavior (p-value = 0.000), where farmers with shorter tenure (≤2 years) were more compliant (78.1%) compared to long-tenure farmers (13.3%). A significant relationship also existed between attitude and PPE use (p-value = 0.000), with none of the negatively-attituded farmers using complete PPE. Knowledge showed no significant relationship (p-value = 0.576). Conclusion: work tenure and attitude are the main determinants of PPE use among pesticide-spraying farmers. Attitude-change and risk normalization interventions should be prioritized to improve PPE compliance.